Romanian Registry of Hypertrophic Cardiomyopathy - overview of general characteristics and therapeutic choices at a national level - Ionilă Paula; Jurcuţ Ruxandra; Ferariu Nicoleta; Roşca Monica; Chivulescu Monica; Mursă Adriana; Militaru Sebastian; Ionescu Alin A.; Căldăraru Cristina; Fruntelată Ana G.; Goanţă Silvia F.; Crişan Simina; et al. (Sciendo, 2018)
Introduction. Hypertrophic cardiomyopathy (HCM) is a disease with increased left ventricular (LV) wall thickness not solely explained by abnormal loading conditions, with great heterogeneity regarding clinical expression and prognosis. The aim of the present study was to collect data on HCM patients from different centres across the country, in order to assess the general characteristics and therapeutic choices in this population.